THE INFLUENCE OF SOCIAL MEDIA ON THE FORMATION OF THE ALONE TOGETHER CULTURE AT THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA - Siti Annisa Marsanda; Elfi Yanti Ritonga (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the influence of the intensity and pattern of social media use on the formation of a culture of alone together among young users. The phenomenon of alone together refers to a condition in which individuals are physically present with others, but are psychologically separated due to the focus on digital devices, especially social media. This study uses a quantitative approach with a survey method of 96 respondents. Data were analyzed using multiple linear regression. The results of the F test showed that all independent variables simultaneously had a significant effect on the culture alone together (Sig. F = 0.000 < 0.05). The t-test showed that several variables had a partial significant influence, namely X1 (frequency of social media access every day), X5 (comfort in expressing oneself on social media), and X8 (habit of checking notifications while studying/studying). An R-Square value of 0.586 indicates that 58.6% of the variation in the culture alone together can be explained by the ten variables studied. These findings indicate that intense social media use may reinforce an individual's tendency to be isolated in social spaces even when physically with others. This study recommends the need for increased digital literacy and awareness of the importance of direct social interaction to maintain balance in modern social life.